Establishing and Utilising In Vitro Lung Models to Demonstrate Peptide Mediated Non-Viral Delivery - Smith, Lauren (2022)
Despite their success as gene therapy delivery systems, viral vectors have some unresolved issues; pathogenicity, immunogenicity, and off target effects can be detrimental and sometimes even oncogenic. Commercialised vectors can also still come with a higher price point.